2022
DOI: 10.3389/fncel.2022.835800
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific B Cell and Anti-Myelin Autoantibody Response After Peripheral Nerve Injury

Abstract: Immunotherapy holds promise as a non-addictive treatment of refractory chronic pain states. Increasingly, sex is recognized to impact immune regulation of pain states, including mechanical allodynia (pain from non-painful stimulation) that follows peripheral nerve trauma. This study aims to assess the role of B cells in sex-specific responses to peripheral nerve trauma. Using a rat model of sciatic nerve chronic constriction injury (CCI), we analyzed sex differences in (i) the release of the immunodominant neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…No sexual dimorphism was observed in MBP 84-104 release ( Lee et al, 2022 ), interaction with Ncoa1 or regulation of LXR post-CCI. Sex- and injury-dependent changes in LXR ligands likely determine sex specificity and degree of anti-nociceptive LXR/RXR action.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…No sexual dimorphism was observed in MBP 84-104 release ( Lee et al, 2022 ), interaction with Ncoa1 or regulation of LXR post-CCI. Sex- and injury-dependent changes in LXR ligands likely determine sex specificity and degree of anti-nociceptive LXR/RXR action.…”
Section: Discussionmentioning
confidence: 92%
“…As a result of our prior extensive biochemical, cell biological and functional analyses ( Chernov et al, 2018 ; Hong et al, 2017 ; Ko et al, 2016 ; Kobayashi et al, 2008 ; Lee et al, 2022 ; Liu et al, 2012 ; Remacle et al, 2018 ), we identified the bioactive 84–104 region of MBP proteolytically released between days 3 and 27 post-CCI ( Fig. 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations